Association between sleep duration and chest pain in US adults: A cross-sectional study - Wei Chen; Ji-ping Wang; Zi-min Wang; Peng-Cheng Hu; Yu Chen (Frontiers Media S.A., 2022)
ObjectiveHerein, we purposed to explore the association of sleep duration with chest pain among adults in US.MethodsThis research work enrolled 13,274 subjects in the National Health and Nutrition Examination Survey (NHANES) from 2011 to 2018. The association of sleep duration with chest pain among adults in US was evaluated by Multivariable logistic regression.ResultsTo elucidate the association, we made adjustments for gender, BMI, diabetes, smoking status, drinking status, race, marital status, annual family income, hyperlipoidemia, Hypertension. Chest pain incidence decreased by 5% [OR = 0.95 (0.93, 0.98), p = 0.0004] for an increase in sleep duration by 1 h. A generalized additive model (GAM) was used to reseal a U-shaped relationship of sleep duration with incident chest pain. When duration of sleep was <6.5 h, chest pain incidence negatively correlated to sleep duration [OR = 0.77 (0.72, 0.82) P < 0.0001]. However, when sleep duration was ≥6.5 h, chest pain incidence rose with escalating sleep duration [OR = 1.07 (1.03, 1.11) p = 0.0014].ConclusionsDuration of sleep was established to be independently linked with an increase in the occurrence of chest pain. Excessive sleep, as much as insufficient sleep, increases the risk of chest pain. Both excessive sleep and insufficient sleep are associated with an increased risk of chest pain.